Ação de micocinas produzidas por Wickerhamomyces anomalus sobre Malassezia pachydermatis isoladas do conduto auditivo de cães - Silva, Jessica Cassia da (2021)
Malassezia pachydermatis has a zoophilic origin and can be found in mammals, and frequently in dogs, in which it mainly colonizes the ear canal region, leading to otitis that is difficult to treat. The mycocins produced by Wickerhamomyces anomalus are capable of inhibiting the growth of eukaryotic and prokaryotic microorganisms. This work aimed to verify the inhibition of M. pachydermatis isolated from the ear canal of dogs, through the action of mycocins produced by W. anomalus. The results showed, by the microdilution broth test, that 100% of M. pachydermatis strains tested were inhibited when culture supernatant containing mycocies was used. The viability test showed that the time required for mycocins to make 100% of M. pachydermatis strains in Sabouraud broth was 8 hours. In the proteinases production test, 44% of the tested strains were strong producers of proteinases. And subsequently, all of these strains that had their enzyme activity strongly positive were inhibited when tested in culture medium containing a subinhibitory concentration of β-glucanases. Thus, the results reinforce the antimicrobial potential of mycocins.